Examining the reliability of discharge ICD coding in the Red Cross War Memorial Children's Hospital administrative database - Daniels, Adriaan (Department of Paediatrics and Child Health, 2019)
Background: Discharge diagnostic data from hospital administrative databases are often used to inform decisions relating to a variety of vital applications. These may include the allocation of resources, quality of care assessments, clinical research and for the formulation of healthcare policy to name a few. Having accurately coded and reliably captured discharge data for patients is of paramount importance for any hospital and health system to function efficiently. Objectives: 1. Retrospectively examine the reliability of the ICD discharge coding in the Red Cross War Memorial Children’s Hospital (RCWMCH) administrative database for primary and secondary discharge diagnoses. 2. Formulate recommendations for improvement to the current system. Methods: This study was a retrospective folder review of 450 patient admissions to the short stay and general paediatric wards at the RCWMCH between 1 August 2013 and 1 September 2014. International Classification of Diseases version 10 (ICD-10) discharge coding was completed for each admission by the principal investigator and compared with the corresponding admission data captured for each patient within the Clinicom® Health Information System. Agreement comparison was done to both four-character and three-character ICD-10 code specificity. Results: Of the initial 450 randomly selected folders, 396 (88%) were analysed during the folder review process. The median number of total diagnoses (primary diagnosis plus secondary diagnoses) coded by the principal investigator (PI) folder review was 3 with a distribution of 1 to 10 (IQR 2 - 4). The median number of total diagnoses coded in Clinicom® was 1 with a distribution of 1 to 3 (IQR 1 - 1). Agreement of primary diagnosis coding to four characters was 26.3% with slight improvement to 34.3% when assessed to three characters. Agreement for secondary diagnoses to four characters was 14.9% and 27.7% when assessed to three characters. Conclusion: Reliability of administrative discharge data from RCWMCH is poor. Inadequacies with regard to the employment of dedicated and/or adequately trained coding personnel may be significant contributors to the problem.